Homeland Political Trust Among Emigrants: The Case of Finland-Swedes - Isak Vento (Frontiers in Political Science, 2021)
How does emigrating affect one's political trust for their native country's political and state institutions? This question is increasingly relevant as a result of growing migration in the wake of globalization and the willingness to widen electoral laws and channels for participation to also include emigrated citizens in homeland politics. Despite the research conducted on homeland politics and voting from abroad in political science, the question of homeland political trust among emigrants has not been given sufficient attention. This could be seen as surprising from the perspective of trust research, which has exhaustively analyzed political and social trust. This paper seeks to map the effect of migration on political trust by comparing the trust in Finnish political and state institutions of emigrated Swedish-speaking Finns, also known as Finland-Swedes, and Finland-Swedes living in Finland. The Finland-Swedes are a resourceful minority with a sizeable diaspora, which in relative terms is comparable to nations with a renowned diaspora. The paper analyzes the political trust of migrants and residents with two high quality random surveys and using two methods, linear regression and propensity score matching, with analysis of average treatment effects to counter potential endogeneity of political trust and migrating citizens. The analyses show emigrants have on average significantly higher homeland political trust. Comparing the linear regression analysis and the average treatment effects after matching we get similar results, although the linear regression analysis that controls for potentially endogenous factors seems to somewhat exaggerate the effect of migration.